Analysis of Financing Strategy in the Era and Post COVID-19 (Case Study of PT. Mandiri Tunas Finance) - Kalimah, Siti; agustin, Riska; Khayati, Ismatul (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2023)
The COVID-19 pandemic is a global challenge that affects the economy, including the performance and the function of financial institutions in Indonesia. PT. Mandiri Tunas Finance (MTF) has increased in credit risk and decreased in the sales volume in 2020 by 45.75% compared to 2019 before COVID-19. However, post COVID-19, MTF has succeeded in implementing strategies to improve its credit risk and sales volume. The purpose of this research is to identify and to analyze the implementation of marketing strategies and MTF credit restructure in saving customers' bad credit in the era and post COVID-19. This study uses a descriptive qualitative research methods. Data was collected through interviews, documentation and analysis of financial reports. Sampling was done by purposive sampling technique. In case of sales decline, MTF implemented a more active marketing strategy based on the components of Kotler's marketing strategy, namely segmenting, targeting and positioning, which had an impact on MTF's sales volume, which increased in 2021 by 34.98% and in 2022 increased by 47%. 77% compared to the previous year. In the case of bad credit and customer default, the solution is to restructure credit according to the customer's condition. This has an impact on the movement of the NPF ratio from 2019 to 2022 under 1%.